PREDICTION OF BANKRUPTCY LEVELS USING THE ALTMAN Z-SCORE METHOD IN BANKING COMPANIES ON THE INDONESIA STOCK EXCHANGE FOR THE 2018-2021 PERIOD - sari wahyuni (Indragiri Research Center (ingreat), 2023)
This research was conducted at banking companies listed on the Indonesia Stock Exchange from 2018 to 2021 with the aim of knowing the condition of the company using the modified almant z-score method. The population in this study is 45 companies but only 5 companies that meet the sample criteria. This type of research is descriptive with a quantitative approach. The type of data used is quantitative data and qualitative data, while the data source used in this study uses secondary data in the form of financial reports for the last 4 years. The variables used in this research are Working Capital to total Assets (X1), Retained Earning to Total Assets (X2), Earning Before Interest Taxes to Total Assets (X3), and Market value of Equity to Book Value of Liabilities (X4). This research data analysis uses the almant z-score method as a tool to predict corporate bankruptcy. The results of this study indicate that from 2018 to 2021 there is one banking company that is in an unhealthy condition or is included in the bankrupt company category, namely Bank Mega tbk (MEGA) with an average value of -3.32. And there are four companies that are not bankrupt or in good health, including Bank Negara Indonesia (persero) tbk (BBNI) with an average Z-Score of 4.49, Bank Bukopin tbk (BBKP) with an average Z-Score of 4.57, Bank Mandiri (persero) tbk (BMRI) with an average Z-score of 4.38, and Bank Rakyat Indonesia tbk (BBRI) with an average Z-Score of 4.62 .